Automatic generation control of a two area power system implementing IDDF controller under restructured environment - Sinha, Sayantan; Kumar Mallick, Ranjan; Mohapatra, Monalisha; Kumar Giri, Rohit (International Journal of Engineering and Technology, 2018)
This paper presents the Automatic generation control of an interlinked power system in a restructured environment. The model consists of a hydro plant, a thermal plant and a diesel plant incorporated in both areas. The Area Control Error (ACE) is minimized with the help of a new controller called the Integral Double Derivative controller (IDDF) employed as a secondary controller in the proposed model. The controller parameters are optimized by a novel optimization scheme called the Lightning Search Algorithm. The proposed model is simulated under two market scenarios. The robustness of the system is also examined under step load perturbations, random loading conditions and parameter variation. The settling time of the IDDF controller is put to comparison with the PID controller and the supremacy is established.Â